REALIZATION OF VICTIM JUSTICE THROUGH EFFECTIVE PROSECUTION- AN INDIAN PERSPECTIVE - Raizada, Mukul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Despite the Human Rights discourse resulting in the recognition of a ‘positive obligation’ upon the State to provide a mechanism using substantive and procedural measures, to ensure the victim’s right to justice, the adversarial criminal justice system is not the ideal place where the victim’s right to fair trial may be realized. Trends show that there is more receptibility to the idea of granting the ‘service rights’ to the victim of crime within the criminal justice system but still, there is a reluctance to grant the victim a status as a party in the criminal justice process. This article argues that the victim’s right to justice, inclusive of the right to a fair trial, is recognized in the Indian criminal justice system but is not effectively translating into implementation. This article looks into the reasons why the public nature of the criminal trial and the structural compulsions do not leave much scope for a meaningful role that the victim might espouse for realizing his right to a fair trial. It is also trying to find out to what extent the Indian Criminal Justice System has measured up to fulfilling the State’s Obligations towards fair trial rights of the victims of crime.